1994
DOI: 10.1111/j.1600-0609.1994.tb00650.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum homocysteine as a predictor for vitamin B12 or folate deficiency

Abstract: Tissue deficiency of vitamin B12 and folate results in an increase in serum homocysteine (sHcy). We have measured sHcy in patients with reduced serum vitamin B12 and/or red cell folate (RCF) to determine its usefulness as a discriminant for the diagnostic interpretation of reduced vitamin levels. Of 3846 patients who had serum vitamin B12 and RCF assayed, 335 (9%) had reduced vitamin levels. Multivariate analysis showed a significant association between sHcy and serum creatinine (p = 0.0001), positive intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…74 Anomalies to homocysteine fine-tuning are known to be related to oxidative stress 74 and deficiency B-group vitamins. 75 However, no substantial alteration of vitamin intake was observed (retinol -vitamin A, riboflavin -vitamin B2 -Fig. S2, ESI †).…”
Section: Molecular Biosystems Papermentioning
confidence: 99%
“…74 Anomalies to homocysteine fine-tuning are known to be related to oxidative stress 74 and deficiency B-group vitamins. 75 However, no substantial alteration of vitamin intake was observed (retinol -vitamin A, riboflavin -vitamin B2 -Fig. S2, ESI †).…”
Section: Molecular Biosystems Papermentioning
confidence: 99%
“…All the patients in the current study were on B vitamin supplements. Therefore, given the importance of B vitamins for homocysteine metabolism, we think that adequate B vitamins might have promoted the conversion of homocysteine to cysteine or methionine [ 26 , 27 ] and thereby prevented homocysteine elevation in the patients of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Another extensive study on children with autism compared with controls found low serum tryptophan, high serum glutamate and homocysteine, and significantly reduced free sulfate, as well as high levels of oxidative stress markers,[ 1 ] all of which are consistent with these assertions. High serum homocysteine is one associated consequence of folate deficiency:[ 76 ] Folate is produced by Lactobacillus and Bifidobacteria from products of the shikimate pathway. [ 240 ]…”
Section: Ammonia Glutamate and Neurotoxicitymentioning
confidence: 99%